1996
DOI: 10.1063/1.363508
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lattice vibration in fine particles of barium titanate single crystal including the lattice hydroxyl group

Abstract: Fine particles of barium titanate single crystal with an average particle size of about 66 nm were prepared by a hydrothermal method. In the as-prepared sample, there was a large amount of the hydroxyl group and barium vacancy, and its crystal structure was assigned to cubic with an expanded lattice using a Rietveld method. The hydroxyl group desorbed with increasing calcination temperature, especially desorbing remarkably in the range from 200 to 300 °C. Above 700 °C, there was no hydroxyl group in the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 48 publications
6
119
1
Order By: Relevance
“…This band was not observed in sintered NaLaTi 2 O 6 confirming that all the O-H containing species are removed upon heating (note that sintering NaCeTi 2 O 6 causes phase separation so IR of that sample was not recorded). Similar results are reported in the literature for perovskites prepared hydrothermally [58,68,70,71]. Noma et al observed a sharp band at around 3500 cm -1 in hydrothermal BaTiO 3 , which they attributed to lattice hydroxyl groups occupying the oxide sites, and a broad band from 3000-3600 cm -1 which was ascribed to surface-adsorbed hydroxyl groups, present either as hydroxide or as water.…”
Section: Resultssupporting
confidence: 85%
“…This band was not observed in sintered NaLaTi 2 O 6 confirming that all the O-H containing species are removed upon heating (note that sintering NaCeTi 2 O 6 causes phase separation so IR of that sample was not recorded). Similar results are reported in the literature for perovskites prepared hydrothermally [58,68,70,71]. Noma et al observed a sharp band at around 3500 cm -1 in hydrothermal BaTiO 3 , which they attributed to lattice hydroxyl groups occupying the oxide sites, and a broad band from 3000-3600 cm -1 which was ascribed to surface-adsorbed hydroxyl groups, present either as hydroxide or as water.…”
Section: Resultssupporting
confidence: 85%
“…For the synthesis of a pure, homogeneous and nanometric level of BTO, wet chemical routes have been used, which have huge economic advantages over the conventional manufacturing methods (solid-solid reaction) [7][8][9]. As an alternative, Raman spectroscopy is a powerful experimental tool for studying the lattice vibrations and other elementary excitations in materials, providing important information about the structure, composition, strain, defects, and phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The value of remnant polarization is increased with increasing milling duration. The value of remnant polarization is much higher as compared to that obtained from solid -state reaction method`2 7 . Piezoelectric coefficients of the studied samples is shown in Table 1.…”
Section: Ferroelectric and Piezoelectric Studiesmentioning
confidence: 68%
“…BaTiO 3 nanocrystals have been synthesized by various techniques like hydrothermal method 6,7 , sol-gel processing 8 oxalate route 9 and polymeric precursor methods 10 . Although BaTiO 3 nanoparticles produced by these methods are smaller than 100 nm, they contain residual hydroxide ions 11,12 .…”
Section: Introductionmentioning
confidence: 99%